Dynamics of post-training coaching leadership implementation: a case study of first-line managers in a private hospital - Dharmawan P Hadad (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to explore the dynamics of coaching skills implementation among first-line managers following their participation in the “Coaching for Leaders” training program in a private hospital setting. A qualitative approach with a case study design was employed to gain an in-depth understanding of participants’ experiences. Data were collected through semi-structured in-depth interviews, non-participant observations, and document analysis involving eight first-line managers. The data were analyzed using thematic analysis based on the interactive model of Miles, Huberman, and Saldana. The findings reveal that although participants have developed a basic understanding of coaching principles, the implementation of coaching skills remains partial and situational. Coaching practices are primarily applied in specific contexts, such as one-on-one interactions and performance evaluations, rather than being consistently integrated into daily leadership practices. The study identifies several barriers to implementation, including habitual directive leadership styles, time constraints, high workload, and limited staff readiness. At the same time, intrinsic motivation, positive initial experiences, and peer support are found to facilitate the implementation process. Furthermore, the study highlights positive impacts at managerial, staff, and team levels, including increased self-awareness, improved communication, and enhanced staff initiative. However, these impacts are not consistently observed across all units. This study contributes to the literature by providing a contextual and in-depth understanding of post-training coaching implementation in healthcare settings and emphasizes the importance of organizational support in sustaining behavioral change.